Kazakhstan-EU Relations in the Realities of the Russo-Ukrainian War: Textual Analysis Before and After the Start of the War - Irzhanova, S.S.; Murzagulova, K.A.; Ordabayeva, D.B. (International School of Economics Maqsut Narikbayev University, 2024)
Global security concerns have contributed to both the domestic and foreign policy directions of international actors. The Russo-Ukrainian war, as an instance of an unexpected and significant military crisis, affected relations between Kazakhstan and political players, particularly the European Union. This research aims to answer how the Russo-Ukrainian war impacted the dynamics of Kazakhstan's relations with the EU. The previous description of Kazakhstan’s partnership with the EU includes democratisation initiatives and energy trade. Moreover, the majority of studies highlight inefficient attempts to propagate foundations of democratic governance and significant interest in Kazakhstan’s energy potential. This study is concentrated on Kazakhstan-EU relations after the beginning of the Russo-Ukrainian war. It consists of two studies: an analysis of press materials and a qualitative content analysis with some quantitative approach. It focuses on the 191 press materials from the European External Action Service from 2018-2021 and 2022-2024 for the first part of the study, and 2018-2021, 2022, and 2023-2024. Ultimately, the intensification of Kazakhstan-EU relations in the energy sector was identified as a result of geopolitical realities. The content analysis demonstrates the active engagement of the EU in cooperation with Kazakhstan during 2022, particularly in areas of energy, economy and democratisation. This year also marked a crucial development in cooperation in the renewable energy sector.
Keywords: Kazakhstan, the European Union, cooperation, the Russo-Ukrainian war, energy, democratisation, economy